Truncating mutations in SHANK3 associated with global developmental delay interfere with nuclear β‐catenin signaling. Issue 3 (16th April 2020) - Hassani Nia, Fatemeh; Woike, Daniel; Kloth, Katja; Kortüm, Fanny; Kreienkamp, Hans‐Jürgen
Abstract: Mutations in SHANK3, coding for a large scaffold protein of excitatory synapses in the CNS, are associated with neurodevelopmental disorders including autism spectrum disorders and intellectual disability (ID). Several cases have been identified in which the mutation leads to truncation of the protein, eliminating C‐terminal sequences required for post‐synaptic targeting of the protein. We identify here a patient with a truncating mutation in SHANK3, affected by severe global developmental delay and intellectual disability. By analyzing the subcellular distribution of this truncated form of Shank3, we identified a nuclear localization signal (NLS) in the N‐terminal part of the protein which is responsible for targeting Shank3 fragments to the nucleus. To determine the relevance of Shank3 for nuclear signaling, we analyze how it affects signaling by β‐catenin, a component of the Wnt pathway. We show that full length as well as truncated variants of Shank3 interact with β‐catenin via the PDZ domain of Shank3, and the armadillo repeats of β‐catenin. As a result of this interaction, truncated forms of Shank3 and β‐catenin strictly co‐localize in small intra‐nuclear bodies both in 293T cells and in rat hippocampal neurons. On a functional level, the sequestration of both proteins in these nuclear bodies is associated with a strongly repressed transcriptional activation by β‐catenin owing to interaction with the truncated Shank3 fragment found in patients. Our data suggest that truncating mutations in SHANK3 may not only lead to a reduction in Shank3 protein available at postsynaptic sites but also negatively affect the Wnt signaling pathway. Abstract : Full‐length Shank3 interacts with β‐catenin at postsynaptic sites. Mutations in the SHANK3 gene found in patients with autism and intellectual disability lead to expression of a truncated Shank3 protein. The lack of Shank3 synaptic targeting elements leads to recruitment of Shank3 and β‐catenin to nuclear bodies, where activation of the Wnt signaling pathway by β‐catenin is blocked by the truncated Shank3 fragment.